A Retrospective Observational Study to Assess Prescription Pattern in Patients with Type B Aortic Dissection and Treatment Outcome. (1st August 2016) - Liao, Kuang-Ming; Chen, Chung-Yu; Wang, Shih-Han; Huang, Jiann-Woei; Kuo, Chen-Chun; Huang, Yaw-Bin
Abstract : Aortic dissection is a life-threatening condition. However, the use of medication to treat it remains unclear in our population, particularly in patients with a type B aortic dissection (TBAD) who do not receive surgery. This retrospective cohort study evaluated antihypertensive prescription patterns and outcomes in patients with nonsurgical TBAD. We reviewed the hospital records of patients with TBAD at a medical center in Taiwan from January 2008 to June 2013 to assess the baseline information, prescribing pattern, event rate, and clinical effectiveness of different antihypertensive treatment strategies. A Cox proportional hazards model was used to estimate outcomes in different antihypertensive strategies. The primary endpoints were all-cause mortality and hospital admission for an aortic dissection. We included 106 patients with a mean follow-up period of 2.75 years. The most common comorbidity was hypertension followed by dyslipidemia and diabetes mellitus. Study endpoints mostly occurred within 6 months after the index date. Over 80% of patients received dual or triple antihypertensive strategies. Patients treated with different treatment strategies did not have a significantly increased risk of a primary outcome compared with those treated with a monotherapy. We found no significant difference in the primary outcome following the use of different antihypertensive medication regimes.